Historia oral de la colonia Melchor Ocampo en Morelia: memoria e historicidad - Álvarez Estrada, Jesús Modesto (Universidad Michoacana de San Nicolás de Hidalgo, 2022)
The present investigation interprets the history of the colonia Melchor Ocampo de Morelia through the methodology of oral history, in other words, it considers as the main source for the analysis of the past the stories of the people who lived through the different events of this territory, these were obtained using the interview technique and were recorded for later examination. From this analysis of the oral source (comparison, saturation and triangulation) it was found out which elements of the past are important and compositional of the identity of colonia Melchor Ocampo, these are: the first neighbors and their socioeconomic condition; housing problems and basic services; spaces and ways of socializing and masculinity, violence and territory. In the same way, it´s analyzed the reasons why this particular history, and others in the same situation, that are not present in the hegemonic historical discourse, that latter which has sometimes considered insignificant everything that remains outside of today's so-called "historic center", so that although the research is focused on the history of a specific neighborhood, it responds to the material and symbolic framework of the city. Now, it is considered that the lack of importance mentioned is related to the motivations of the person who enunciates, given that the history of the Melchor Ocampo had and has great importance for the neighbors, an example of this is the neighborhood group that has been created to rescue and revalue the past of the neighborhood.

La presente investigación interpreta la historia de la colonia Melchor Ocampo de Morelia mediante la metodología de la historia oral, es decir, considera como fuente principal para el análisis del pasado los relatos de las personas que vivieron los distintos acontecimientos de este territorio, estos se obtuvieron mediante la técnica de la entrevista y fueron grabados para su posterior examinación. De este análisis de la fuente oral (comparación, saturación y triangulación) se logró conocer que elementos del pasado son importantes y compositivos de la identidad de la colonia Melchor Ocampo, los cuales son: los primeros vecinos y su condición socioeconómica; problemas de vivienda y servicios básicos; espacios y formas de socialización y masculinidad, violencia y territorio. Asimismo, se analizan los motivos por los cuales esta historia particular, y otras más en la misma situación, no están presentes en el discurso histórico hegemónico, este último en ocasiones ha considerado intrascendente todo lo que queda fuera del hoy llamado “centro histórico”, de forma tal, que, si bien la investigación se centra en la historia de una colonia en específico, esta responde al entramado material y simbólico de la urbe. Ahora bien, se considera que la intrascendencia señalada se relaciona con las motivaciones de quien enuncia, dado que la historia de la Melchor Ocampo, tuvo y tiene gran importancia para los vecinos, ejemplo de esto, es la agrupación vecinal que se ha creado para rescatar y revalorar el pasado de la colonia.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; IIH-M-2022-0849; Colonias; Historia urbana; Oralidad; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/8423